Pengaruh Good Corporate Governance (GCG) dan profitabilitas terhadap nilai perusahaan - Putri, Bella Danita; Putri, Eskasari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the influence of Good Corporate Governance (GCG) and profitability on firm value. In this case good corporate governance is proxied by the managerial ownership, independent board of commissioners, audit committee, profitability is proxied by Return On Asset (ROA) while firm value is proxied by Price Book Value (PBV). The population in this study are food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2020 period. The sampel in this study was fixed by purposive sampling method so that was found 83 samples. The type of data used in this study is secondary data with the data collection method is documentation method. The analysis used in this study is multiple linear regression analysis. Based on the results of study, it can be concluded that independent board of commissioners and profitability have an effect on firm value, while managerial ownership and audit committee have no effect on firm value.